Environmental law and sustainability (Legal journal - Research in Legal and Social Sciences, 2017)
This work seeks to find appropriate tools to deal with a serious problem: deforestation, which brings with it dire consequences for the entire planet and which in a very direct way manifests itself on the population, causing significant difficulties in health, in industrial production , agricultural, livestock, tourism etc. and demonstrate through the analysis and data obtained through satellite images, that the requirements aimed at improving said situation are not met and, in this way, take appropriate measures, as each case warrants. In the department of Canindeyú and, especially in the district of Nueva Esperanza, there are still many kinds of plant formations that constitute a source of life, in addition to offering multiple uses as energy and industrial raw materials. In said department, deforestation has been growing alarmingly and there have been few efforts to raise awareness or carry out concrete actions to protect environmental resources, which are of collective or general interest (diffuse rights), that is, they belong to everyone and not are not only limited to this generation, but also to future generations. It follows that the responsibility does not fall only on the authorities created for this purpose; there must be solidarity and co-responsibility at the local, departmental, national and, finally, global levels.
Keywords: deforestation; sustainability; Environment